2020
DOI: 10.3390/ph13080199
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Molecular Imaging Agents Targeting Bradykinin B1 and B2 Receptors

Abstract: Kinins, bradykinin and kallidin are vasoactive peptides that signal through the bradykinin B1 and B2 receptors (B1R and B2R). B2R is constitutively expressed in healthy tissues and mediates responses such as vasodilation, fluid balance and retention, smooth muscle contraction, and algesia, while B1R is absent in normal tissues and is induced by tissue trauma or inflammation. B2R is activated by kinins, while B1R is activated by kinins that lack the C-terminal arginine residue. Perturbations of the kinin system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 106 publications
0
23
0
3
Order By: Relevance
“…The kallikrein-kinin system may also provide an exciting approach for diabetes treatment. It has been shown that bradykinin (BK) resulted in increased glucose uptake and insulin sensitivity through the bradykinin type 2 receptor (BK2R) signaling ( Lau et al, 2020 ). In addition, studies on diabetic mice models treated with human tissue kallikrein 1 gene resulted in lowered glucose concentration, controlled hypoglycemia, and reversed insulin resistance ( Kolodka et al, 2014 ).…”
Section: Novel Drug Targetsmentioning
confidence: 99%
“…The kallikrein-kinin system may also provide an exciting approach for diabetes treatment. It has been shown that bradykinin (BK) resulted in increased glucose uptake and insulin sensitivity through the bradykinin type 2 receptor (BK2R) signaling ( Lau et al, 2020 ). In addition, studies on diabetic mice models treated with human tissue kallikrein 1 gene resulted in lowered glucose concentration, controlled hypoglycemia, and reversed insulin resistance ( Kolodka et al, 2014 ).…”
Section: Novel Drug Targetsmentioning
confidence: 99%
“…Recent reports (32)(33)(34) have suggested a potential role of the B1 receptor in various pathophysiological processes. For example, it may be implicated in inflammation, hyperalgesia, hyperthermia and experimental diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…B1R, however, is induced and upregulated during tissue injury involving the cytokine pathway, oxidative stress, and the transcriptional nuclear factor NF-κB [2,38,39,[42][43][44]. The highly inducible character of B1R is often symptomatic of the occurrence of autoimmune, infectious, cardiac, kidney, and bowel inflammatory diseases [2,[45][46][47][48][49]. However, B1R may play a compensatory role for the lack of B2R, and its upregulation during tissue damage may be a useful mechanism of host defense [25,[50][51][52].…”
Section: Kinin Receptorsmentioning
confidence: 99%
“…Indeed, BK induces vascular endothelial cadherin phosphorylation and a subsequent rapid internalization and ubiquitination, leading to an opening of endothelial cell junctions and plasma leakage [134] (Figure 2). However, more studies are needed in DR using recently developed selective and stable B2R antagonists or biostable kinin analogs [41,46,135].…”
Section: Kallikreins and Kinin Receptors In Diabetic Retinopathymentioning
confidence: 99%